Wisdom of Indigenous and Tacit Knowledge for Disaster Risk Reduction - Furqan Ishak Aksa (Faculty of Geography, Universitas Gadjah Mada, 2020)
This article aims to identify the types of knowledge needed in reducing the risk of disasters and challenges in applying knowledge. Based on the literature review, this article analyzes various kinds of knowledge, the process of knowledge creation, and the challenges of knowledge transmission. Basically, knowledge consists of explicit and tacit knowledge. In the context of disasters, most of the knowledge is tacit in individual local people (indigenous knowledge). Tacit knowledge can motivate someone to make decisions (act) when a disaster occurs. To be understood and disseminated to the wider community, tacit knowledge needs to be converted into explicit knowledge and scientifically validated. This article proposes the importance of integrating tacit knowledge in the form of local knowledge to become explicit knowledge so it can be widely used. Knowledge built in a bottom-up manner, which comes from local knowledge, is believed to be effective in disaster risk reduction. However, in some countries, the process of applying the knowledge is constrained by a fatalism that is influenced by social culture and religious beliefs.